UTILIZATION OF V-EDUSPACE IN ENHANCING STUDENTS' UNDERSTANDING AND CRITICAL THINKING OF SOLAR SYSTEM MATERIALS - Melly Sri Wahyuni; Atep Sujana; Isrok'atun (Jurnal Cakrawala Pendas, 2024)
This research is motivated by the inappropriate use of learning media and the lack of use of technology, resulting in low learning outcomes, where in the 21st century learning emphasizes the use of technology. This is based on the fact that in the field there are still many teachers using inappropriate learning media, resulting in students not understanding the material and hampering students' ability to develop their critical thinking skills. The purpose of this study is to determine the level of conceptual understanding and critical thinking skills of students after using the V-Eduspace application in solar system learning. This study used quasi-experimental design research with non-equivalent control group. The sample of the research consists of 68 students in grade VI. Data collection techniques through two tests, namely the concept comprehension test and the critical thinking test. Data analysis using SPSS 29. The results showed that learning the solar system by utilizing the V-Eduspace application obtained higher assessment results compared to learning without the application. Therefore this application is able to further improve understanding and critical thinking skills. And proven by the results of the N-gain test, the effectiveness of using the V-Eduspace application in learning is in the high category.